AN ANALYSIS OF ACEHNESE EFL STUDENTS' GRAMMATICAL ERRORS IN WRITING RECOUNT TEXTS - Qudwatin Nisak M. Isa; Risdaneva Risdaneva; Affied Alfayed (Englisia: Journal of Language, Education, and Humanities, 2017)
This study aims at finding empirical evidence of the most common types of grammatical errors and sources of errors in recount texts written by the first-year students of SMAS Babul Maghfirah, Aceh Besar. The subject of the study was a collection of students' personal writing documents of recount texts about their lives experience. The students' recount texts were analyzed by referring to Betty S. Azar classification and Richard's theory on sources of errors. The findings showed that the total number of error is 436. Two frequent types of grammatical errors were Verb Tense and Word Choice. The major sources of error were Intralingual Error, Interference Error and Developmental Error respectively. Furthermore, the findings suggest that it is necessary for EFL teachers to apply appropriate techniques and strategies in teaching recount texts, which focus on past tense and language features of the text in order to reduce the possible errors to be made by the students.